Evaluation of Economic Feasibility of Limestone Mining Di PT. Cement Bosowa Maros Maros Regency South Sulawesi Province - Donda, Ivanna Elisa; Hidayatullah Shidiq,; Faisol Mukarom, (ReTII, 2022)
PT. Semen Bosowa is one of the companies engaged in the industrial sector in terms of supplying building raw materials, namely cement with a production capacity of 4.2 million tons/year. Economic feasibility evaluation is carried out to find out what composition is used in determining the feasibility evaluation of limestone mining. PT. Semen Bosowa which has been operating for 24 years. In this study, the evaluation was carried out for 5 years from 2022-2026. The method used to calculate cash inflows and outflows is Discounted Cash Flow by using economic feasibility parameters Net Present Value (NPV), Internal Rate of Return (IRR) and Pay Back Period PBP. The capital structure used is 60% own capital 40% loan capital and the discount factor used comes from the WACC calculation of 18%. The results of the analysis conducted by NPV of Rp.93,669,293,085, IRR 98% and PBP 1.07 years. Sensitivity analysis of both operations and income at a decrease of 5% to an increase of 10% shows the lowest value of NPV and IRR is Rp. 67,415,665,068 and 77% in the condition of cost of income -10% with PBP 1.34 years. This value is still above the discounted rate of 18% so it can be concluded that economically the limestone mining of PT. Semen Bosowa in the period 2022-2026 is able to continue. Keywords: feasibility, NPV, IRR, PBP